How to know who you are through your short video selfies?—Capturing personality via short video selfies - Dong, Zhiwen; Xie, Tian (Frontiers in Psychology, 2023)
The extant literature has accumulated enormous knowledge on personality prediction from digital records on social networking sites (e.g., photo selfies). However, little is known about how short video selfies reflect their owner’s personality and how people judge others’ personalities from short video selfies. Taking short video selfies is very popular today; many people are willing to share their short video selfies with others. Based on the lens model theory, it is expected that one’s personality is associated with short video selfies. By analyzing 177 Chinese TikTok (Douyin in China) users’ short video selfies and their Big Five personalities, it showed that specific cues in short video selfies related to agreeableness, conscientiousness, neuroticism, and openness. But only extraversion could be predicted by short video selfies accurately. This study is the first to reveal personality-related cues in short video selfies and has practical implications for both short video platforms and their users.